(untitled) (CIPEEX, 2026)
Pulmonary rehabilitation is considered an essential treatment for smokers, as it improves respiratory function, muscle strength, and quality of life. Evidence indicates that the practice of breathing exercises and physiotherapeutic interventions helps reduce symptoms and increase functional capacity. Objective: To evaluate the effects of pulmonary rehabilitation on respiratory function and quality of life in smokers. Method: This is an integrative literature review conducted in four databases, which, after article screening, resulted in the inclusion of recent and relevant studies on pulmonary rehabilitation in smokers. Results: Pulmonary rehabilitation improves functional capacity, reduces dyspnea, and supports smoking cessation in smokers with chronic lung diseases. Conclusion: Pulmonary rehabilitation shows potential to enhance respiratory function, quality of life, and functional capacity in smokers, reinforcing the role of physiotherapy as a preventive and therapeutic strategy in respiratory care.